2014
DOI: 10.1002/stem.1827
|View full text |Cite
|
Sign up to set email alerts
|

Reptin Regulates Pluripotency of Embryonic Stem Cells and Somatic Cell Reprogramming Through Oct4-Dependent Mechanism

Abstract: Oct4 has been implicated in regulation of pluripotency in embryonic stem cells (ESCs) and reprogramming of somatic cells into induced pluripotent stem cells. However, the molecular mechanisms involved in Oct4-dependent regulation of pluripotency and reprogramming have not been clear. To gain insight into the mechanism of regulation of Oct4-mediated self-renewal of ESCs and reprogramming of somatic cells, we attempted to identify Oct4-binding proteins using affinity purification and mass spectrometry. We identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Previous reports have shown that the recruitment of Pontin/Reptin complex increases the transcriptional response of Myc 31 and Oct4 (ref. 32 ), suggesting that this complex modulates transcriptional activity in a number of different cellular and molecular contexts. Mechanistically, Pontin and Reptin are related to a family of AAA + ATPase helicases and they display multiple functions such as the regulation of transcription, DNA repair and chromatin remodelling protein 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that the recruitment of Pontin/Reptin complex increases the transcriptional response of Myc 31 and Oct4 (ref. 32 ), suggesting that this complex modulates transcriptional activity in a number of different cellular and molecular contexts. Mechanistically, Pontin and Reptin are related to a family of AAA + ATPase helicases and they display multiple functions such as the regulation of transcription, DNA repair and chromatin remodelling protein 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Using the Lipofectamine-Plus reagent (Life Technologies), pMXs-green fluorescent protein (GFP), pMXs-OCT4, pMXs-SOX2, pMXs-KLF, and pMXs-c-MYC were transfected into prepared PLAT-GP cells (2.5 × 10 4 cells/cm 2 ) with gag-pol and VSV-G [17]. At 4 h after transfection, the medium was replaced with DMEM with 10% FBS.…”
Section: Methodsmentioning
confidence: 99%
“…Pontin activation of Oct4 targets is thought to be mediated by recruitment of p300 acetyltransferase (Boo et al, 2015 ). Reptin was also found to maintain pluripotency of ESCs, perhaps acting in complex with Pontin (Do et al, 2014 ) (Table 2 ).…”
Section: Role Of Pontin/reptin In Specific Cellular Pathwaysmentioning
confidence: 99%